Enhancing Transplanting Success in Restoration of Degraded Areas Using Peat-Free Substrates - Silvia Traversari; Sara Di Lonardo; Simone Orsenigo; Daniele Massa; Beatrice Nesi; Lino Zubani; Sonia Cacini (Plants)
Native plant species used for ecological restoration in urban and degraded areas are typically cultivated by ornamental and forestry nurseries. In the face of climate change, it is crucial to produce plants that can withstand transplant stress while promoting the use of sustainable materials, such as peat-free substrates. Replacing peat with locally sourced organic materials offers a promising strategy to enhance plant resilience to abiotic stress while improving sustainability. This study evaluated the effects of alternative growing media on the growth and post-transplant performance of Viburnum lantana L. under standard nursery conditions. Three substrate mixtures were tested: (i) peat:pumice 70:30 v:v (PP); (ii) coconut coir dust:pumice 70:30 v:v (CP); (iii) coconut coir dust:green compost 55:45 v:v (CGC). After one year in the nursery, half of the plants were sampled in late spring for biometric, eco-physiological, and nutrient analyses, while the remaining plants were transplanted into a degraded area providing only a single irrigation event during the trial. Approximately 100 days after transplant, biometric and eco-physiological parameters were assessed. Plants grown on CGC demonstrated the highest transplant success, while those grown on PP and CP exhibited greater leaf necrosis, with PP plants also showing significant defoliation. These findings highlight CGC as a viable and sustainable alternative to peat-based substrates, particularly for post-transplant survival in degraded areas prone to drought stress.